Variability of anti-Müllerian hormone and folliculotropic hormone levels in women of reproductive age in relation to normal or impaired ovarian function - Jusiakowska-Piputa, Małgorzata; Kaczmarek, Maria (Anthropological Review, 2025)
The demographic crisis in Europe is growing due to an increasing proportion of couples with fertility disorders. The purpose of this study was to examine the variability of ovarian reserve markers with age in women with premature ovarian insufficiency (POI) and polycystic ovary syndrome (PCOS) in relative to women with normal ovarian function. Two hormones were analyzed: anti-Müllerian hormone (AMH) and folliculotropic hormone (FSH). This study demonstrates that AMH is a valuable indicator of alterations in reproductive capacity. FSH is a standard marker of the hypothalamic-pituitary-ovarian axis.We examined the reproductive status of 390 women aged 23–46 years in three groups. Ovarian dysfunction was determined by a medical diagnosis. The study includes women with PCOS (n=154), POI (n=40), and control group (n=196) with normal ovarian function (NOF). Blood samples were collected to measure AMH and FSH. We used multivariate logistic regression analysis to demonstrate the relationship between hormone levels and age in different age groups. ANOVA was used to analyze factors related to AMH and FSH concentrations. The results confirmed that women with POI had significantly lower AMH concentrations and higher FSH concentrations than women with normal ovarian function only in the group of women aged 36–46 years. There were no statistically significant differences in FSH levels in women with POI and NOF in the 23–30 and 31–35 age groups. AMH levels were higher in the PCOS group than in women with NOF in all age groups. FSH marker did not differ compared to the control group in women aged 23–30 and 36–46. The predictive value of AMH in the diagnosis of PCOS is significantly higher than the commonly used FSH. The results may contribute to earlier assessment of biological status to support reproductive chances in women with POI and PCOS.